Comprehensive audit of gastrointestinal endoscopy adverse events: Emphasizing quality indicators and economic impact with the AIG-AGREE modification - Katrevula, Anudeep; Singla, Neeraj; Rughwani, Hardik; Jagtap, Nitin; Katukuri, Goutham Reddy; Godbole, Shubhankar; Teles de Campos, Sara; Memon, Sana Fathima; Inavolu, Pradev; Singh, Aniruddha Pratap; Mathur, Sonam Siddhant; Ashraf, Aadil; Patel, Rajendra; Haja, Azimudin; Asif, Shujaath; Katamareddy, Thejesh; Kalapala, Rakesh; Ramchandani, Mohan; Lakhtakia, Sundeep; Santosh, Darisetty; Reddy, Nageshwar (Endoscopy International Open, 2024)
Background and study aims: This study aimed to conduct a clinical audit of adverse events (AEs) arising from gastrointestinal endoscopy, utilizing the AGREE classification for AEs and establishing its correlation with the ASGE classification. This study further integrated the economic repercussions of AEs into the AGREE classification through the AIG-AGREE modification.Patients and methods: A prospective observational study was conducted at the Asian Institute of Gastroenterology, Hyderabad, India, from July 1, 2021, to December 31, 2021. The study included all patients who underwent diagnostic or therapeutic endoscopic procedures. AEs were categorized using the American Society of Gastrointestinal Endoscopy (ASGE) and AGREE classifications. A quality indicator questionnaire containing 15 questions was graded based on the latest ASGE and European Society of Gastrointestinal Endoscopy guidelines. The grading scale ranged from 1 to 3 (poor), 4 to 6 (average), 7 to 9 (excellent), to 10 (outstanding). In addition, the AIG-AGREE modification divided the economic impact into five scales (α, β, γ, δ, and ε) based on multiples of the baseline amount. (ClinicalTrials.gov Identifier: NCT05228353)Results: Over the 6-month study period, a total of 42,471 endoscopic procedures were performed, identifying 220 AEs. Analysis revealed a significant positive correlation (Pearson correlation coefficient = 0.79; P < 0.001) between the grades of AEs in the AGREE and ASGE classifications. The median score for all quality indicators was 8, indicating excellent services based on feedback from 13,042 surveyed patients. Notably, patients with more severe AEs (AGREE III-V) exhibited higher economic impact categories (β, γ, δ, ε) compared with those with less severe AEs (AGREE I-II).Conclusions: The AIG-AGREE modification stands as a pioneering effort that highlights the importance of considering economic factors in the evaluation of AEs in gastrointestinal endoscopy.
Keywords: Quality and logistical aspects; Quality management; Performance and complications